Modeling and Analysis of Product Evaluation Using Star Ratings, Reviews, and Helpfulness Metrics - Lopez, Benjamin (Journal of Computer Science and Software Applications, 2022)
In this study, we begin with data preprocessing and subsequently conduct a thorough analysis. This allows us to establish a relational model encompassing Star Ratings, Reviews, and Helpfulness Metrics. Utilizing these relational models, we then develop a robust product evaluation framework.